Bronchodilator Response of FEV6 and FEV3 as Surrogates of Forced Vital Capacity - Mehrparvar, Amir Houshang (National Research Institute of Tuberculosis and Lung Disease, 2014)
BACKGROUND: Spirometry as a non-invasive and inexpensive test is widely used for occupational health evaluations. Bronchodilator test is used for the assessment of airflow limitation and increase in forced expiratory volume in 1 second (FEV(1)) or forced vital capacity (FVC) is considered as a positive response. This study was performed to assess the response of forced expiratory volume in 6 seconds (FEV(6)), forced expiratory volume in 3 seconds (FEV(3)), and forced expiratory time (FET) to bronchodilator administration. MATERIALS AND METHODS: In this cross-sectional study, the response of FEV(3), FEV(6), FEV(1)/FEV(3), FEV(1)/FEV(6) and FET to bronchodilator administration was assessed in subjects referred to Yazd occupational medicine clinic regardless of their diagnosis. The average increase in spirometric parameters (i.e. FVC, FEV(1), FEV(1)/FVC, FEV(3), FEV(6), FEV(1)/FEV(3), FEV(1)/FEV(6) and FET) was measured. The difference between baseline and post-bronchodilator spirometries was assessed by calculating absolute change and change from baseline as well. Data analysis was done by Student's t test, chi square test and Pearson's correlation test. RESULTS: Totally 104 subjects were entered in the study. FEV(1) showed the highest response to bronchodilator. FVC response to bronchodilator was correlated with FET, but such correlation was not observed for FEV(6) and FEV(3). The mean increase in FEV(6), FEV(3), and FET after bronchodilator administration was 50.90 ml (2.23%), 110.51 ml (3.08%) and -1.85 s, respectively. CONCLUSION: FVE(6) can be used as a substitute for FVC for the assessment of bronchodilator response without the need for FET adjustment.